Biological Effect from Mobile Phone to Human Head and Brain - พ่วงศรี ปิยะภัทร; ฉัตรภูติ นนชณัต; พฤกษานุบาล อภิบาล (RMUTL Engineering Journal, 2018)
This article describes research entitled the simulation of effect from mobile phone to human head and brain. Based on three variables, they are comprised of electrical properties, averaged mass tissues of human head and brain and frequencies of electromagnetic wave from the phone. The results of this simulation are power pattern of mobile phone, Specific Absorption Rate (SAR) and power loss density in human head. The research uses Flat Specific Anthropomorphic Mannequin (SAM) combined with IEEE mobile phone. The two methods named Perfect Boundary Approximation (PBA) and Thin Sheet Technique (TST) are used to be mesh dividing. Finite Difference Time Domain numerical method is used to analyze. The results are found that SAR values in all conditions are in the range of 0.013-9.95 W/kg. The second point, the SAR values are increased according to averaged mass tissues and frequencies. Then, the area of SAR values of 1800 MHz is the narrowest due to - 60 degree Main Lobe direction. Finally, the power loss density varies directly with frequencies.